Sariki Momo of Ikot Esetang. Ikot Ekpene District – Petition against the Agent of U. A. C. Store, Ikot Ekpene (Colonial Letters and the Contact of Knowledges, 1935)
This file contains colonial letters on the petition of Sariki Momo of Ikot Esetang against U. A. C. Store, Ikot Ekpene
Keywords: Archives; Colonisation; Letters; Social norms; Discourse analysis; Petitions; British Colonisation; Colonial Records; Southern Cameroons; Postcolonial Heritage; Great Britain; Postcolonial Studies